REPRESENTASI TOLERANSI ANTAR UMAT BERAGAMA DAN PLURALISME DALAM FILM KOS-KOSAN - Pristiawan, Taufik Rizqi; Yusmawati, Yusmawati (Media Bahasa, Sastra, dan Budaya Wahana, 2024)
This research discusses the role of the film "KOS-KOSAN" in raising the theme of inter-religious tolerance and pluralism in a pluralistic Indonesian society. Film is considered a powerful medium in conveying messages and social values. Through strong narratives, complex characters, and evocative visuals, films can stimulate reflection and awareness of the importance of tolerance and inter-religious harmony. These films can inspire and convey values of tolerance, mutual respect, and inter-religious harmony to their audiences. This study aims to analyze representations the values of tolerance between religious communities of pluralism in the film “KOS-KOSAN”. In this study, Roland Barthes semiotic method approach was used to analyze the elements in the film, especially signs that are an important part of everyday life. The results of the study show that the film "KOS-KOSAN" succeeds in depicting several aspects that contain values of tolerance and pluralism in the context of everyday life, such as: respect for religious differences and choices of clothing, acceptance of multiculturalism and diverse lives, acceptance of multiculturalism and diverse lives, Clothing symbolism and respect for identity. Keywords: Film; pluralism; representation; tolerance